2019
DOI: 10.17159/2520-9868/i77a06
|View full text |Cite
|
Sign up to set email alerts
|

Reducing practice-shock: First-year student teachers' experiences of a campus-based teaching practice model

Abstract: Most initial teacher education programmes include a compulsory teaching practice module and there are various models that could be used for first-year students' teaching practice. In South Africa, the Minimum Requirements for Teachers Education Qualification document provides guidelines for teaching practice in initial teacher education programmes, but it does not include specific implementation guidelines. To address this gap, a campus-based teaching practice model to prepare and support first-year students w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Some behaviours take much more time to be learned (i.e., learning to be resilient and vulnerable) than a two-year teacher-preparation program allows. However, increasing research (Caires et al, 2009;Delemarter, 2015;Moosa, 2019;Stokking et al, 2003) on specific efforts to reduce practice shock has demonstrated increased ECT retention. Our recommendation for teacher preparation programs is to provide teacher candidates with awareness: implicit discussions on the realities of teaching that will alleviate practice shock, and to intentionally include discussions on extraneous contexts, such as an FN school community and potential situations for BIPOC teachers.…”
Section: Our Recommendationsmentioning
confidence: 99%
“…Some behaviours take much more time to be learned (i.e., learning to be resilient and vulnerable) than a two-year teacher-preparation program allows. However, increasing research (Caires et al, 2009;Delemarter, 2015;Moosa, 2019;Stokking et al, 2003) on specific efforts to reduce practice shock has demonstrated increased ECT retention. Our recommendation for teacher preparation programs is to provide teacher candidates with awareness: implicit discussions on the realities of teaching that will alleviate practice shock, and to intentionally include discussions on extraneous contexts, such as an FN school community and potential situations for BIPOC teachers.…”
Section: Our Recommendationsmentioning
confidence: 99%
“…WIL is an indispensable part of teacher education which is compulsory and serves as a means of assisting student teachers to experience the classroom practice and atmosphere before starting their careers (Moosa, 2019). Through teaching practice, student teachers are afforded an opportunity to practice what they learnt theoretically during lectures in an authentic classroom context.…”
Section: Work-integrated Learning (Wil)mentioning
confidence: 99%
“…Thus, WIL and teaching practice are usually used interchangeably with concepts such as practicum or teaching experience. Furthermore, the student teachers are also afforded an opportunity to learn from observing their mentor teachers and intervening in and influencing the classroom activities as a whole (Milne, 2006;Moosa, 2019). Thus, the Department of Higher Education set teaching practice as compulsory for all student teachers, with the duration ranging from 20 weeks for BEd and 10 weeks for PGCE students under the supervision of experienced mentor teachers (Du Plessis, 2010;Dreyer, 2015, in Taole, 2015.…”
Section: Work-integrated Learning (Wil)mentioning
confidence: 99%
See 1 more Smart Citation
“…The Teaching Practicum (TP) component of Initial Teacher Education (ITE) programmes was significantly disrupted, as the national lockdown period coincided with the time that many ITE students were engaged withTP in schools. In education, the term 'teaching practicum' is used interchangeably with concepts such as workintegrated learning (WIL), teaching practice, teaching experience, professional training or school-based training (Moosa, 2019). The school-based component of teacher training programmes in Zimbabwe is referred to as the Teaching Practice.…”
Section: Introductionmentioning
confidence: 99%